2010
DOI: 10.1111/j.1463-1318.2009.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab‐based therapy vs noncetuximab therapy in advanced or metastatic colorectal cancer: a meta‐analysis of seven randomized controlled trials

Abstract: Cetuximab-based therapy improves PFS and OS resulting in better ORR vs noncetuximab therapy. Its most common and severe AE is skin toxicity that should be predictable and manageable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Cetuximab was chosen because it is in use for the treatment of certain types of human cancers (33,40), and thus the study could have clinical implications. Compared with untreated controls, cetuximab raised the BP of mice on normal salt diets by 25 mm Hg (120 Ϯ 3 versus 145 Ϯ 2 mm Hg) and that of those on high salt diets by 34 mm Hg (127 Ϯ 3 versus 161 Ϯ 6 mm Hg) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cetuximab was chosen because it is in use for the treatment of certain types of human cancers (33,40), and thus the study could have clinical implications. Compared with untreated controls, cetuximab raised the BP of mice on normal salt diets by 25 mm Hg (120 Ϯ 3 versus 145 Ϯ 2 mm Hg) and that of those on high salt diets by 34 mm Hg (127 Ϯ 3 versus 161 Ϯ 6 mm Hg) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have confirmed the positive effect of rash on the prediction of treatment outcome and survival of patients treated with EGFR inhibitors [ 13 , 20 22 , 41 ]. In this study, a relationship between degree of rash and response to treatment was found ( p = 0.058; n = 49), but it was not statistically significant.…”
Section: Discussionmentioning
confidence: 85%
“…A meta-analysis of seven randomized controlled clinical trials showed that cetuximab and chemotherapy improves OS, PFS, and response rates compared to chemotherapy alone. However, in this meta-analysis cetuximab-related effect was not adjusted for the K-ras tumor status [42].…”
Section: Correlation Between Kras Mutation Status and Prognosismentioning
confidence: 95%